The crisis management in corporate landscape based on multisector in Malaysia: a cross-sectorial review - Yahaya, Nurul Nabilah; Othman, Sarina; Tuan Ismail, Tuan Nooriani (Faculty of Administrative Science and Policy Studies, 2025)
The critical role of effective management during crises has been underscored by the unprecedented challenges posed by the global COVID-19 pandemic, which significantly disrupted corporate operations worldwide. In Malaysia, the pandemic induced substantial financial and operational losses across various industries. In Malaysia, companies under the categories of Government-Linked Companies (GLCs) exhibited more robust crisis management frameworks compared to private sector firms. This paper presents a comprehensive review of the literature on crisis management, focusing on its application within Malaysian companies during periods of crisis and adversity. Additionally, it investigates crisis management practices across diverse sectors to identify key determinants of crisis management effectiveness. In other words, this paper focuses on the multi-sectors of the different companies in Malaysia under the scope of crisis management. The reviews suggest that conventional business models and strategies that historically ensured corporate success are increasingly insufficient under crisis conditions, necessitating adaptive and proactive management approaches to sustain organizational viability during and post-crisis.